Effect of GO, CNTs, and hybrid nanoparticles coated carbon fiber reinforced epoxy composite on erosive wear properties using Taguchi orthogonal array - Singh M.; Dodla S.; Gautam R.K. (My University, 2025)
This study investigates the erosion wear performance of polymer composites reinforced with carbon nanotubes (CNTs), graphene oxide (GO), and hybrid (GO/CNTs) coated carbon fibers, introducing a novel approach to enhance fiber-matrix bonding and load transfer, an underexplored area in erosion wear studies. Unlike previous matrix modification-focused research, this study emphasizes fiber surface modification to improve adhesion and stress transfer efficiency. Solid particle erosion tests assess the impact of nanoparticle coatings, velocity, discharge rate, and impingement angle on wear resistance. Taguchi (L16) and ANOVA analyses identify impact velocity as the most significant factor influencing erosion rates, with hybrid coatings demonstrating superior wear resistance. The lowest erosion rate was observed with hybrid coatings at 20 m/s velocity, 2 g/min discharge rate, and a 15° impingement angle. Tensile testing demonstrated notable mechanical improvements, with hybrid coating attaining a tensile modulus of 33 GPa and a tensile strength of 518 MPa, reflecting 32 % and 33.50 % increases, respectively, compared to uncoated carbon fiber reinforced epoxy composite (CFRE). Scanning electron microscope (SEM) analysis reveals erosion mechanisms, including micro-cutting, plowing, fiber breakage, and matrix debonding. © 2025 Elsevier B.V.